Pf16 and phiPMW: Expanding the realm of Pseudomonas putida bacteriophages. - Damian J Magill; Victor N Krylov; Olga V Shaburova; John W McGrath; Christopher C R Allen; John P Quinn; Leonid A Kulakov (PLoS ONE)
We present the analysis of two novel Pseudomonas putida phages, pf16 and phiPMW. Pf16 represents a peripherally related T4-like phage, and is the first of its kind infecting a Pseudomonad, with evidence suggesting cyanophage origins. Extensive divergence has resulted in pf16 occupying a newly defined clade designated as the pf16-related phages, lying at the interface of the Schizo T-Evens and Exo T-Evens. Recombination with an ancestor of the P. putida phage AF is likely responsible for the tropism of this phage. phiPMW represents a completely novel Pseudomonas phage with a genome containing substantial genetic novelty through its many hypothetical proteins. Evidence suggests that this phage has been extensively shaped through gene transfer events and vertical evolution. Phylogenetics shows that this phage has an evolutionary history involving FelixO1-related viruses but is in itself highly distinct from this group.